A draft genome assembly of the reef-building coral Acropora hemprichii from the central Red Sea - Anna Fiesinger; Carol Buitrago-López; Abdoallah Sharaf; Anny Cárdenas; Christian R. Voolstra (Scientific Data)
Abstract Coral reef ecosystems are under threat from climate change. Thus, active interventions to spur coral conservation/restoration are critical to support reef survival, greatly informed by a molecular understanding of resilience. The genus Acropora is a species-rich and globally prevalent reef builder that has experienced dramatic declines in the Caribbean. Here we generated a draft genome of the common coral Acropora hemprichii from the central Red Sea, one of the warmest water bodies in the world. We assembled the genome using 10x Chromium sequencing with subsequent scaffolding using a reference genome and Illumina short-read sequencing contigs. The A. hemprichii genome has an assembly size of 495.6 Mb confirmed using physical size estimation, of which 247.8 Mb (50%) are repeats. The scaffold N50 is 1.38 Mb with 99.6% of BUSCO genes identified (93.7% complete, 5.9% fragmented), providing a set of 26,865 protein-coding genes. The Red Sea A. hemprichii reference genome provides a valuable resource for studies aiming to decode the genomic architecture of resilience, e.g. through comparative analyses with other Acropora genomes.